Online Teachers Training: Increasing Elementary School Teachers’ Ability in Daily Speaking English for Bilingual - Redjeki Agoestyowati (Ahlimedia Press, 2021)
Bilingual class (Indonesian and English) for some lessons must be done in Islamic Elementary School of Al Azhar 17 Bintaro. Therefore, English Training for teacher was conducted. This program was a challenge for all teachers of SD Al Azhar 17 Bintaro to improve their competence in teaching by using two languages and to improve the ability of using English for daily communication with students. The aims of the training was to prepare the implementation of bilingual classes that was done 10 meetings and each meeting was done 4 hours. English Teacher Training Program include: games and icebreaking, group and class discussions, role-play, sharing session, microteaching (presentation), and feedback evaluation. Participants were always enthusiastic in doing all activities. Feedback from other participants was very good. At the end of the training, there was an increase in the competence of all participants in using English expressions for teaching purposes. They seem more confident and communicate more fluently in English. The school hopes that the bilingual training program in schools will continue to be a success.